Effects of a Short Video–Based Resident-as-Teacher Training Toolkit on Resident Teaching. (October 2017) - Ricciotti, Hope A.; Freret, Taylor S.; Aluko, Ashley; McKeon, Bri Anne; Haviland, Miriam J.; Newman, Lori R.
Abstract : OBJECTIVE: To pilot a short video–based resident-as-teacher training toolkit and assess its effect on resident teaching skills in clinical settings. METHODS: A video-based resident-as-teacher training toolkit was previously developed by educational experts at Beth Israel Deaconess Medical Center, Harvard Medical School. Residents were recruited from two academic hospitals, watched two videos from the toolkit ("Clinical Teaching Skills" and "Effective Clinical Supervision"), and completed an accompanying self-study guide. A novel assessment instrument for evaluating the effect of the toolkit on teaching was created through a modified Delphi process. Before and after the intervention, residents were observed leading a clinical teaching encounter and scored using the 15-item assessment instrument. The primary outcome of interest was the change in number of skills exhibited, which was assessed using the Wilcoxon signed-rank test. RESULTS: Twenty-eight residents from two academic hospitals were enrolled, and 20 (71%) completed all phases of the study. More than one third of residents who volunteered to participate reported no prior formal teacher training. After completing two training modules, residents demonstrated a significant increase in the median number of teaching skills exhibited in a clinical teaching encounter, from 7.5 (interquartile range 6.5–9.5) to 10.0 (interquartile range 9.0–11.5; P <.001). Of the 15 teaching skills assessed, there were significant improvements in asking for the learner's perspective ( P =.01), providing feedback ( P =.005), and encouraging questions ( P =.046). CONCLUSION: Using a resident-as-teacher video-based toolkit was associated with improvements in teaching skills in residents from multiple specialties. Abstract : Using a resident-as-teacher video-based toolkit is associated with improvements in teaching skills in residents from multiple specialties.